Flavonoids profile and antioxidant activity in flowers and leaves of hawthorn species (Crataegus spp.) from different regions of Iran - Abolfazl Alirezalu; Peyman Salehi; Nima Ahmadi; Ali Sonboli; Serena Aceto; Hamid Hatami Maleki; Mahdi Ayyari (International Journal of Food Properties, 2018)
This study was undertaken to determine the total quantity of phenolic and flavonoids, as well as to find out about the HPLC quantification of some individual phenolic compounds (i.e. chlorogenic acid, vitexin 2”-O-rhamnoside, vitexin, rutin, hyperoside, quercetin, and isoquercetin) in flowers and leaves of 56 samples of different hawthorn species (Crataegus spp.) collected from different geographical regions of Iran. The amount of total phenolics ranges from 7.21 to 87.73 mg GAE/g in dry weight of the plant, and the total amount of flavonoids varied amongst species and in different plant organs ranging from 2.27 to 17.40 mg/g dry weight. Chlorogenic acid, vitexin, and vitexin 2”-O-rhamnoside were found to be the most abundant phenolic compounds in the extracts of hawthorn leaves. Meanwhile, chlorogenic acid, hyperoside, and rutin were the most abundant phenolic compounds in the extracts of hawthorn flowers in most genotypes. The antioxidant activity widely varied in species and in different organs of each individual plant, ranging from 0.9 to 4.65 mmol Fe++/g DW plant, calculated through the ferric-reducing antioxidant power (FRAP) method. Thus, this could provide valuable data for developing breeding strategies and plans; it can also help us in selecting genotypes with high phenolic contents for producing natural antioxidants and other bioactive compounds beneficial for food or the pharmaceutical industries.